2010
DOI: 10.1089/ten.tec.2009.0116
|View full text |Cite
|
Sign up to set email alerts
|

On the Determination of Darcy Permeability Coefficients for a Microporous Tissue Scaffold

Abstract: Structural characterization of porous tissue scaffolds is challenging due to their complexity. Most investigators report the porosity of the material together with an estimate of the mean pore size and the pore size distribution. The usefulness of these measures is limited, especially in predicting the time-dependent permeation characteristics of a biodegradable, cell-seeded scaffold. A potential solution to this problem is to measure the permeability of the matrix and determine the Darcy permeability coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…To decrease the likelihood of random protein adsorption and encourage cellescaffold interactions through integrin binding sites, collagen was covalently attached to the surface of PLCL scaffolds. There is concern that protein coating of electrospun polymers may restrict effective aqueous fluid flow, thus disrupting transport of fluids and nutrients through scaffolds in vivo [48]. However, despite the presence of a protein coating, a negligible change in effective permeability was found between ccPLCL and PLCL scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…To decrease the likelihood of random protein adsorption and encourage cellescaffold interactions through integrin binding sites, collagen was covalently attached to the surface of PLCL scaffolds. There is concern that protein coating of electrospun polymers may restrict effective aqueous fluid flow, thus disrupting transport of fluids and nutrients through scaffolds in vivo [48]. However, despite the presence of a protein coating, a negligible change in effective permeability was found between ccPLCL and PLCL scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…The permeability of the tubular scaffolds was determined using Darcy's law [16] by measuring the rate of flow of different fluids through the scaffold wall with a known pressure gradient. The fluid flow rate, Q, (m 3 =s) through the scaffold wall is directly proportional to the cross-sectional area, A, (m 2 ) and the pressure drop P b -P a (Pa) and inversely proportional to the viscosity of fluid, l (N.s=m 2 ) and the length 1 , L (m) over which the pressure differential occurs, as expressed in Eq.…”
Section: Darcy Permeabilitymentioning
confidence: 99%
“…Alternatively, the accessibility of the nutrients to the cells could be extrapolated by the porosity of the membrane, assuming that high porosity involves high nutrients permeability. However, Wang et al [17] realized that in other works this assumption was not always supported by experimental evidences. They already pointed out the interest on experimentally quantifying permeabilities of the scaffolds as a performance parameter of the nutrients and metabolites transport properties.…”
Section: Introductionmentioning
confidence: 91%
“…Table 1 demonstrated that they were significantly lower for BSA filtration than for clean water filtration, with the exception of the M-EtOH/Gly membrane working under TFF mode that had comparable permeances for clean water and BSA solutions filtration. Wang et al [17] observed as well that protein solution permeability was 3 times lower than that of water through microporous PCL tubular scaffolds. In general, the permeance decline of BSA solutions through M-IPA/Gly membranes in comparison with water permeance was higher in NFF operation mode than in TFF mode (Table 1).…”
Section: Statistical Data Treatmentmentioning
confidence: 99%